UJI BEBERAPA VARIETAS KEDELAI DENGAN PUPUK ORGANIK DI TANAH ULTISOL KABUPATEN ACEH TENGGARA - Syariani Tambunan; Nico Sebayang; Neni Marlina; Bambang Sugiyono; Joni Phillep Rompas; Rosmiah Rosmiah; Iin Siti Aminah (Politeknik Negeri Lampung., 2022)
Test Several Soybean Varieties with Organic Fertilizer in Ultisol Soil, Aceh Tenggara District. Soybean production in dry land dominated by Ultisolsin Southest Aceh Regency is still low, namely 1.57-1.58 tonnes ha-1, to increase soybean production, the provision is by planting high yielding superior varieties and providing organic fertilizers which are able to improve soil fertiliyby donating NPK nutrients. This study aims to test several varities of soybeans by applying organic fertilizers. The research was conducted in Gulo Village, Darul Hasanah Subdistrict, which took place from June to October 2019. Factorial Randomized Block Design (RAK) was used with 8 combinations of 4 replications. Factor 1: Organic fertilizers, namely without and organic fertilizers. Factor 2: Several varieties, namely Anjasmoro, Bio Soy 1, Bio Say 2, Devon1 . The results showed that the treatment of organic fertilizers with the Bio Soy 2 variety increased the weight of 100 seeds 166.67%, followed by organic fertilizer with the Bio Soy 1 variety, which was 155.56% when compared to treatment without organic fertilizer with the Devon 1 variety. Furthermore, the soybean varieties Bio Soy 2 and Bio Soy 1 have the potential to be developed in the dry land of Southeast Aceh Regency by appllying organic fertilizers.